KESALAHAN PENGGUNAAN EJAAN DALAM KARANGAN EKSPOSISI SISWA KELAS X MIPA 1 SMA NEGERI 3 KOTA JAMBI - Uli Wahyuni; Mira Munita Sari (Universitas Batanghari, 2020)
This purpose of this research is to describe the errors of spelling in expository composition of class X MIPA 1 at SMA negeri 3 Kota Jambi academic year 2018/2019. This research used qualitative descriptive method. The data of this research was sequence of sentences of students’ writing with spelling errors. The primary data was students’ expository composition of class X MIPA 1 at SMA Negeri 3 Kota Jambi Tahun academic year 2018/2019. Based on the result of the analysis, it can be found that the errors of spelling in expository composition of students’ class X MIPA 1 semeter I SMA negeri 3 kota Jambi tahun ajaran 2018/2019 were 713 errors. The errors of spelling consists of 588 errors of using capital letter in the beginning of the sentence; 4 errors of using capital letter in the beginning of the sentence with direct quote; 10 errors of using capital letter as the first letter of nation name; 2 errors of using capital letter as the first letter of days’ name; 3 errors of capital letter as the first letter of geography;14 errors of capital letter of every word in the title of their composition. Moreover, there following errors of the use of comma is; 60 errors of comma in between of elements of explanation; 4 errors of comma before conjunction; 11 errors of comma behind the conjunction of sentences; 7 errors of comma in separating direct quote from the other parts of the sentence; 2 errors of comma in between of district or country’s name which is written in sequence; 9 errors of comma on the back of the information of the beginning of the sentence which is used to avoid error of reading.